The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ani11061820
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ridden Horse Pain Ethogram to Horses Competing at the Hickstead-Rotterdam Grand Prix Challenge and the British Dressage Grand Prix National Championship 2020 and Comparison with World Cup Grand Prix Competitions

Abstract: The Ridden Horse Pain Ethogram (RHpE) comprising 24 behaviours was developed to facilitate the identification of musculoskeletal discomfort, with scores of ≥8/24 indicating the presence of pain. The median RHpE score for 147 competitors at World Cup Grand Prix events from 2018 to 2020 was three (interquartile range [IQR] 1–4; range 0–7). The aim of the current study was to apply the RHpE to 38 competitors at the Hickstead-Rotterdam Grand Prix Challenge and 26 competitors at the British Dressage Grand Prix Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…Persistent positioning of the head >10° for ≥10 s behind a vertical position was seen with similar frequency in this study (59%) and in 5* three-day event horses (64%) [ 9 ], and was also observed in elite (67%) [ 9 ] and sub-elite (77%) [ 10 ] Grand Prix dressage horses. This is contrary to judging guidelines [ 28 , 29 ] but appears to be inadequately penalised.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Persistent positioning of the head >10° for ≥10 s behind a vertical position was seen with similar frequency in this study (59%) and in 5* three-day event horses (64%) [ 9 ], and was also observed in elite (67%) [ 9 ] and sub-elite (77%) [ 10 ] Grand Prix dressage horses. This is contrary to judging guidelines [ 28 , 29 ] but appears to be inadequately penalised.…”
Section: Discussionsupporting
confidence: 83%
“…The explanation may be multifactorial, reflecting the higher frequency of pain-related gait abnormalities at the lower levels, an overall lower skill level of riding and inferior training. However, repeated tail swishing was seen more often in the 5* level event horses [ 8 ]) compared with horses in the current study, and was also a frequent observation in Grand Prix dressage horses [ 9 , 10 ]. This may be a reaction to stronger application of leg and spur cues by the riders, or the horses experiencing more difficulty with movements requiring a greater level of collection.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations